Rituximab versus cyclophosphamide in ANCA-associated renal vasculitis. - Jones, R; Tervaert, J; Hauser, T; Luqmani, R; Morgan, MD; Peh, C; Savage, C; Segelmark, M; Tesar, V; van Paassen, P; Walsh, D; Walsh, M; et al. (2010)
BACKGROUND: Cyclophosphamide induction regimens for antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis are effective in 70 to 90% of patients, but they are associated with high rates of death and adverse events. Treatment with rituximab has led to remission rates of 80 to 90% among patients with refractory ANCA-associated vasculitis and may be safer than cyclophosphamide regimens. METHODS: We compared rituximab with cyclophosphamide as induction therapy in ANCA-associated vasculitis. We randomly assigned, in a 3:1 ratio, 44 patients with newly diagnosed ANCA-associated vasculitis and renal involvement to a standard glucocorticoid regimen plus either rituximab at a dose of 375 mg per square meter of body-surface area per week for 4 weeks, with two intravenous cyclophosphamide pulses (33 patients, the rituximab group), or intravenous cyclophosphamide for 3 to 6 months followed by azathioprine (11 patients, the control group). Primary end points were sustained remission rates at 12 months and severe adverse events. RESULTS: The median age was 68 years, and the glomerular filtration rate (GFR) was 18 ml per minute per 1.73 m(2) of body-surface area. A total of 25 patients in the rituximab group (76%) and 9 patients in the control group (82%) had a sustained remission (P=0.68). Severe adverse events occurred in 14 patients in the rituximab group (42%) and 4 patients in the control group (36%) (P=0.77). Six of the 33 patients in the rituximab group (18%) and 2 of the 11 patients in the control group (18%) died (P=1.00). The median increase in the GFR between 0 and 12 months was 19 ml per minute in the rituximab group and 15 ml per minute in the control group (P=0.14). CONCLUSIONS: A rituximab-based regimen was not superior to standard intravenous cyclophosphamide for severe ANCA-associated vasculitis. Sustained-remission rates were high in both groups, and the rituximab-based regimen was not associated with reductions in early severe adverse events. (Funded by Cambridge University Hospitals National Health Service Foundation Trust and F. Hoffmann-La Roche; Current Controlled Trials number, ISRCTN28528813.)